Perceived Parental Self-Efficacy Among Mothers of Infants in Neonatal Intensive Care Units: A Descriptive Study - Coşkun, Adnan Batuhan; Öğüt, Nisa; Elmaoğlu, Erhan (AVES, 2025)
Objective: The neonatal intensive care unit (NICU) is a critical yet challenging environment for mothers, often inducing significant stress. Maternal self-efficacy, a vital psychological construct, plays a pivotal role in shaping coping mecha-nisms and caregiving behaviors. Exploring the correlation between maternal stress and perceived parental self-efficacy is essential for optimizing NICU support strategies. To assess the correlation between maternal stress levels and per-ceived parental self-efficacy among mothers of preterm infants in NICUs and to determine the predictors of sociode-mographic factors on these variables.Methods: This descriptive study was conducted with 111 mothers of prterm infants in the Neonatal Intensive Care Unit (NICU) of two private hospitals in Gaziantep, Türkiye, from February to May 2024. Data were collected using a Sociodemographic Information Form, the Parental Stressor Scale: Neonatal Intensive Care Unit, and the Perceived Maternal Parenting Self-Efficacy Scale. Statistical analyses, including t-tests and ANOVA, were utilized to identify signif-icant group differences.Results: Maternal stress levels were significantly influenced by economic status, education, number of pregnancies, and the number of living children. Stress related to the “Infant Appearance and Behaviors” and “Parental Role” sub-scales showed significant associations with factors such as infant gender, birth weight, maternal education, pregnancy complications, and prior NICU admissions. Higher parental self-efficacy scores were positively correlated with lower stress levels and were significantly influenced by similar sociodemographic variables.Conclusion: This study underscores the importance of sociodemographic factors and parental self-efficacy in deter-mining maternal stress levels in NICUs. Tailored, family-centered interventions focusing on enhancing maternal self-ef-ficacy and addressing socioeconomic challenges are essential to reducing stress and improving outcomes for both mothers and preterm infants.
Keywords: Family-centered care; maternal stress; neonatal intensive care unit; parenting self-efficacy; preterm infants